2006
DOI: 10.1103/physrevc.74.064610
|View full text |Cite
|
Sign up to set email alerts
|

Natural nuclear reactor at Oklo and variation of fundamental constants: Computation of neutronics of a fresh core

Abstract: Using modern methods of reactor physics we have performed full-scale calculations of the natural reactor Oklo. For reliability we have used recent version of two Monte Carlo codes: Russian code MCU REA and world wide known code MCNP (USA). Both codes produce similar results. We have constructed a computer model of the reactor Oklo zone RZ2 which takes into account all details of design and composition. The calculations were performed for three fresh cores with different uranium contents. Multiplication factors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
142
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 40 publications
2
142
0
Order By: Relevance
“…That the typical correction to the resonant energies is of the order of 10 MeV (×δ NN ), compared to the resonant energies themselves which are around 0.1 MeV, allows one to put relatively strong constraints on any variation. This is reminiscent of the case of the resonance producing an excited state of 150 Sm of importance in setting constraints on the variation in couplings using the Oklo reactor (Shlyakhter 1976;Damour & Dyson 1996;Fujii et al 2000;Olive et al 2002;Petrov et al 2006). In that case, the resonant energy is 0.1 eV compared to corrections of about 1 MeV due to changes in the fine structure constant, leading to limits on Δα em /α em of the order of 10 −7 .…”
Section: Sensitivity Of the 3 α-Reaction Ratementioning
confidence: 99%
See 1 more Smart Citation
“…That the typical correction to the resonant energies is of the order of 10 MeV (×δ NN ), compared to the resonant energies themselves which are around 0.1 MeV, allows one to put relatively strong constraints on any variation. This is reminiscent of the case of the resonance producing an excited state of 150 Sm of importance in setting constraints on the variation in couplings using the Oklo reactor (Shlyakhter 1976;Damour & Dyson 1996;Fujii et al 2000;Olive et al 2002;Petrov et al 2006). In that case, the resonant energy is 0.1 eV compared to corrections of about 1 MeV due to changes in the fine structure constant, leading to limits on Δα em /α em of the order of 10 −7 .…”
Section: Sensitivity Of the 3 α-Reaction Ratementioning
confidence: 99%
“…This is the case for the fine structure constant for which the constraintα em /α em = (−1.6 ± 2.3) × 10 −17 yr −1 at z = 0 has been obtained from comparing aluminium and mercury single-ion optical clocks (Rosenband et al 2008). On a longer timescale, it was demonstrated that α em cannot have varied by more than 10 −7 over the last 2 Gyr from the Oklo phenomenon (Shlyakhter 1976;Damour & Dyson 1996;Fujii et al 2000;Olive et al 2002;Petrov et al 2006;Flambaum & Wiringa 2009) and over the last 4.5 Gyr from meteorite dating (Dicke 1959;Dyson 1972;Fujii & Iwamoto 2003;Olive et al 2004). At higher redshift, 0.4 < z < 3.5, there are conflicting reports of an observed variation of α em from quasar absorption systems.…”
Section: Introductionmentioning
confidence: 99%
“…For t = 2×10 9 yr, a time interval of the order of magnitude of the operation of the Oklo natural nuclear reactor, we get: This variation is extremely small and it is difficult to measure (Petrov et al, 2006;Meshik et al, 2004;Gauthier-Lafaye, 2002;De Laeter et al, 1980). We expect that the processing of the cosmological data we possess, as well as the improvement of the observational instruments, will give us a more accurate value for the fundamental parameter W. However, this more accurate measurement cannot considerably affect the theoretical prediction about Oklo's reactor, since Equation 72 gives an extremely small value for the ratio α α ∆ .…”
Section: On the Oklo Natural Nuclear Reactormentioning
confidence: 99%
“…Other limits on the values of particle couplings and masses at (relatively) recent epochs arise from nuclear physics effects in the Oklo natural reactor at z ≃ 0.2 [20,21] and from long-lived β decay isotopes in meteorites [22]. Direct comparisons of atomic clocks at periods of a few years in the laboratory have also led to strong bounds at the level of 10 −15 per year fractional variation [23].…”
Section: Introductionmentioning
confidence: 99%